Involvement of redox status and the nuclear-related factor 2 in protecting against cadmium-induced renal injury with Sana Makki (Cassia senna L.) pre-treatment in male rats - ALBASHER,GADAH (2020)
Abstract This study was designed to investigate the potential defensive strategy of Sana Makki extract (SME) against Cd-induced in vivo nephrotoxicity and its underlying mechanisms. Male albino rats were used in a thirty days study comparing control, SME-treated, CdCl2-treated, and combined SME and Cd treatment. Pre-treatment with SME significantly reduced serum kidney biomarkers (urea and creatinine), the concentration of renal KIM-1, and kidney index values. Additionally, SME also attenuated CdCl2-induced oxidative and nitrosative stress in renal tissue; significantly reducing malondialdehyde (MDA) and nitric oxide (NO) concentrations and significantly increasing antioxidant enzymes in kidney tissue. Molecularly, SME significantly upregulated antioxidant gene expression (SOD2, GR, GPx1, and CAT) caused by Cd. Notably, the augmented mRNA expression of nuclear-related factor 2 (Nrf2) by Cd was enhanced by SME administration. SME markedly suppressed the Cd-induced rise in pro-inflammatory cytokines. The combination of Cd and SME relieved the Cd-induced apoptotic damage by enhancing Bcl2 and suppressing Bax and Cas-3 levels in renal tissue. The renal tissue histoarchitecture confirmed the biochemical and molecular findings. Collectively, our data indicate that SME can counteract Cd-induced renal intoxication through anti-oxidative, anti-inflammatory, and anti-apoptotic mechanisms.